Development Model of Augmented Reality: A Need Analysis of Vocabulary Book for ESP Students - Husna, Nida; Maulidya, Reza Anis; Hidayat, Didin Nuruddin (Makassar State University, 2024)
Abstract. The real challenge in 5.0 society requires meeting the needs of future generations who can use foreign languages and master technology. This study investigated the need for specific learning sources or materials for vocational students specifically majoring in Informatics Engineering in vocabulary learning. Since vocabulary is a fundamental language aspect of using English in reciprocal communications, this study is a type of survey research that uses quantitative and qualitative data analysis techniques. The instruments used to obtain the data were developed referring to the principal notion of a need assessment proposed by Hutchinson and Waters, validated by a language expert, and served through a questionnaire. The setting of this study involved 48 students of Vocational Students of Informatics Engineering at a private vocational school in Jakarta, Indonesia. The results showed that students of Informatics Engineering at vocational schools must be able to communicate in English, both written and spoken, using the specific term related to their department. Besides studying ESP to work, some students planned to continue to higher education with expertise in linear education. Therefore, they need to learn vocabulary with the integration of technology as they are supposed to deal with it in their field of work in informatics engineering to join the 5.0 society with the advancement of augmented reality-based media. Keywords: Technology, Augmented Reality, Vocabulary, English for Specific Purposes, Vocational School